Key ambidextrous IT governance mechanisms for successful digital transformation: A case study of Bank Rakyat Indonesia (BRI) - Rahmat Mulyana; Lazar Rusu; Erik Perjons (Digital Business, 2024)
Many organizations tried to accelerate their digital transformation, but some of them failed, possibly due to poor governance. Previously the influence of ambidextrous IT governance mechanisms on digital transformation and organizational performance were studied. However, there is a need to investigate what are the key ambidextrous IT governance mechanisms that lead to a successful digital transformation and how they are implemented. A case study was conducted at BRI to address the problem. BRI is an incumbent bank that recently won numerous awards. The case study was chosen to investigate one instance in detail to discover contextual understanding that might not have become apparent priorly. The data was collected by semi-structured interviews triangulated with internal documents until data saturation. Subsequently, the collected data underwent thematic analysis. The findings revealed seven key ambidextrous IT governance mechanisms, encompassing board and executive, strategy and architecture, talent and culture, data and information, development and operation, internal and external collaborations, as well as risk and audit. The study also examined how BRI digital transformation dimensions (digital transformation strategy, strategic alignment, digital and IT assets, knowledge and capability, and innovation culture) impacted organizational performance. Lastly, BRI's organizational performance achievements were examined using operational excellence, customer experience, industry presence, and financial return dimensions. This study offers valuable research insights by exploring the key ambidextrous IT governance mechanisms that influence digital transformation and organizational performance. The study also provides the practical implications on how to implement key ambidextrous mechanisms toward a successful digital transformation, including its organizational performance achievements.
Keywords: 650; Bank Rakyat Indonesia (BRI); Case study; Digital transformation; Key ambidextrous IT governance; Organizational performance